2019
DOI: 10.3122/jabfm.2019.05.190047
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Telephone Visits and Rurality on Veterans Perceptions of Access to Primary Care

Abstract: The objectives of this study were to examine if self-reported access to primary care is associated with actual patient wait times and use of telephone visits, and to assess whether this relationship differs by rural residence. Methods: This study used 2016 administrative data from 994 primary care clinics within the Veterans Health Administration. Multiple-linear regression was used to examine relationships between patient perceptions of access and average actual patient wait time, use of telephone visits, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Patient perceptions regarding the use of nontraditional encounters, such as telephone visits, may differ depending on other access‐related factors such as clinic wait time. A previous study found that veterans served by rural clinics with higher wait times perceived the use of telephone visits more positively in terms of creating access to routine care compared to veterans served by urban clinics 33 . Providing care that addresses the unique needs of patients while incorporating their personal preferences is central to the PCMH model.…”
Section: Discussionmentioning
confidence: 99%
“…Patient perceptions regarding the use of nontraditional encounters, such as telephone visits, may differ depending on other access‐related factors such as clinic wait time. A previous study found that veterans served by rural clinics with higher wait times perceived the use of telephone visits more positively in terms of creating access to routine care compared to veterans served by urban clinics 33 . Providing care that addresses the unique needs of patients while incorporating their personal preferences is central to the PCMH model.…”
Section: Discussionmentioning
confidence: 99%
“…1 , 2 Access is foundational to building patient trust with providers, obtaining preventive care; conversely, poorer outcomes are associated with delayed or missed care. 3 Earlier studies have focused on patient-level correlates of access 4 – 9 and clinic-level interventions intended to improve patients’ access to care such as advanced access 10 12 or patient-centered medical homes. 13 15 Nonetheless, primary care clinic leaders face ongoing challenges to ensuring timely access to needed care given varied resources, challenges, and local contexts.…”
Section: Introductionmentioning
confidence: 99%